CM 2023
DOI: 10.18137/cardiometry.2022.25.743755
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Customer Grocery Shopping Behaviour Amid Covid-19 Pandemic

Abstract: Purpose: The paper attempts to understand and analyze the factors that influence different types of end consumer’s behavior while shopping for groceries both online and offline, considering the Covid-19 pandemic situations. Design/ Method/ Approach: A sample size of 145 members of age varying from 18 to 60 were surveyed through a digital form of a questionnaire. Few factors which generally impact the customer’s shopping behavior were categorized into six different factors: Purchase, Personal, Behavioral, Opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For FMCG brands, especially in Nigeria, this meant communicating the value of their products and the safety measures they were implementing across the supply chain. Rushi and Pradhan (2022) highlighted the changing dynamics of customer grocery shopping behavior during the pandemic. Their study revealed that factors such as product quality, hygiene practices followed by the delivery personnel, and the representation of products on websites or applications became paramount.…”
Section: Safety-first Promotions and Campaignsmentioning
confidence: 99%
“…For FMCG brands, especially in Nigeria, this meant communicating the value of their products and the safety measures they were implementing across the supply chain. Rushi and Pradhan (2022) highlighted the changing dynamics of customer grocery shopping behavior during the pandemic. Their study revealed that factors such as product quality, hygiene practices followed by the delivery personnel, and the representation of products on websites or applications became paramount.…”
Section: Safety-first Promotions and Campaignsmentioning
confidence: 99%